Sustaining community living of the very old: medical and service issues - Collen L. Johnson
The unprecedented prolongation of life in the United States has been accompanied by increased numbers of disabled people in their 80s and 90s, who have high needs for health care and social services. The paper reports longitudinal findings on 150 individuals, 85 years and older. Over three years, their functioning on activities of daily living significantly declined at the same time that they continued to described their health as good and to report contentment about their life. Families were active in sustaining community living of the oldest old, but those most at risk of institutionalization were the childless. Over time, 48% of the survivors stayed functionally fit, while 28% became increasingly disabled and dependent and 24% remained stable at a high level of disability. The means by which the oldest old coped with their disabilities include practical steps in simplifying their environment and narrowing their social world. They also used cognitive regulation by modifying their health beliefs and delimiting those areas over which they could exert a sense of control.